Perancangan Sistem Layanan Pengaduan Masyarakat Pada Kantor Pertanahan Kabupaten Asahan - Liestya Arista Kusuma (Jurnal Riset Multidisiplin Edukasi, 2025)
The Land Office of Asahan Regency faces challenges in managing public complaints, which are still handled manually. This results in inefficient, non-transparent, and less accountable service processes. This study aims to design a web-based public complaint service system to facilitate the community in submitting complaints and to assist the Land Office in recording and processing complaints more effectively. The research methods used include interviews, field research, and literature studies. The designed system includes features such as complaint data management, complaint submission by the public, responses from the administrator, and real-time complaint status monitoring. The implementation of this system is expected to improve efficiency, transparency, and accountability in the management of public complaints at the Land Office of Asahan Regency.